Pola komunikasi antarpribadi dalam membangun kepercayaan diri pasca perselingkuhan masa pacaran - Nisrina Zulfa Hanan; Siswantini (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study seeks to explore how interpersonal communication patterns are utilized in the process of restoring self-confidence in young adults who have experienced infidelity during their dating lives. A descriptive qualitative approach with a phenomenological study was used to gain a deeper understanding of the informants' real-life experiences. The study subjects included individuals aged 18-25 who had experienced infidelity in their dating lives. Sampling was conducted using purposive sampling, and data collection was conducted through in-depth interviews and light observation, with the focus of the study focused on changes in communication after the infidelity. The recovery process is understood to be shaped by several communication patterns that emerge throughout the journey. Supportive communication with the closest social circle, interpersonal communication with spiritual aspects, and managing self-image and communication boundaries to protect psychological well-being and rebuild trust are all achieved through consistency in new relationships. Honest, responsive, and empathetic communication patterns have been shown to help subjects regain self-confidence.The recovery process is seen not only as a matter of healing wounds but also as a way for communication to slowly recover and learn to accept the situation. These findings demonstrate that recovery after infidelity is a long journey through open communication and support from those around them.